Impact of stress on nurses in the healthcare industry. (8th July 2019) - Vrontis, Demetris; El-Chaarani, Hani; Nemar, Sam El; Khalaf, Dounia
Employee performance has become an important factor in a company's success and development. Facing occupational stress in various working fields, especially nursing, seems to be an increasing challenge lately. This research investigates the environmental, situational, and individual factors that affect nurses' level of stress. It also measures the impact of stress on nurses' work performance. The data collected from 100 nurses in different hospitals shows a positive relationship between environmental and situational factors and a nurse's stress and a non-significant correlation between personal factors and nurse stress is found. The results also reveal a positive correlation between stress and overall nurse performance.